Remission of Vulvar Pain Among Women With Primary Vulvodynia. Issue 1 (January 2015) - Nguyen, Ruby H.N.; Mathur, Charu; Wynings, Erin M.; Williams, David A.; Harlow, Bernard L.
Abstract Objective To determine whether rates of remission differed among women with primary versus secondary vulvodynia. Methods Using a community-based observational study based in Minneapolis/St. Paul, 138 clinically confirmed cases of vulvodynia between 18 and 40 years old were classified as primary (vulvar pain starting at the time of sexual debut or first tampon insertion) or secondary (vulvar pain starting after a period of pain-free intercourse) and queried regarding their pain history to determine whether they had ever experienced any vulvar pain-free time (remission) or pain-free time lasting 3 months or longer. Results Remission prevalence was 26% (9/34) for women in the shortest quartile of duration of vulvar pain (<3.8 y) and 38% (13/34) for the longest quartile of duration (≥13 y). After adjusting for vulvar pain duration, generalized vestibular pain, medical treatment, body mass index, and history of pregnancy, women who had primary vulvodynia were 43% less likely to report remission (95% CI = 0.33–0.99) than women with later onset (secondary cases). The association was strengthened when restricting to only remissions lasting 3 months or longer (adjusted risk ratio = 0.43, 95% CI = 0.22–0.84). Generalized vestibulodynia and obesity also reduced the likelihood of remission. Conclusions Our study underscores the heterogeneity of vulvodynia and provides evidence that primary vulvodynia may have a less wavering course and, as such, a potentially different underlying mechanism than that of secondary vulvodynia.